COMPARATIVE ANALYSIS OF LEADING SECTORS IN THE HINTERLAND AREA OF NUSANTARA'S CAPITAL CITY - Diana Maswardani; Agit Budiman; Aceu Nur Dini Riya; Dodi Tirtana (Universitas Negeri Semarang, 2025)
The relocation of Indonesia's capital from Jakarta to the Capital City of Nusantara (Ibu Kota Negara/IKN) in East Kalimantan aims to address development inequality and promote equitable economic growth. As IKN’s hinterland, Balikpapan City, Samarinda City, Kutai Kartanegara District, and Paser District are crucial in supporting this vision. This study analyzes the comparative advantages and potential sectors for development in these areas using a quantitative approach with secondary data from 2010 to 2023. Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analyses identify key sectors, and an overlay analysis is used to conclude which sectors are the leading sectors, visualized through Tableau. Balikpapan has 12 base sectors, with manufacturing, transportation, and warehousing as the strongest. Samarinda has 14 base sectors, led by finance and other services. Kutai Kartanegara District and Paser District rely on agriculture, forestry, fisheries, mining, and quarrying. Forecasting suggests all sectors in these regions have the potential to become leading industries. Balikpapan City and Samarinda City should optimize the service and industrial sectors, while Kutai Kartanegara District and Paser District must diversify beyond primary industries. This strategy supports inclusive and sustainable growth, aligning with the Sustainable Development Goals (SDGs) and shaping future IKN policies.